2005
DOI: 10.1111/j.1467-8276.2005.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Impacts of Intellectual Property Protection in the Seed Industry

Abstract: We examine the welfare impact of different intellectual property protection (IPP) regimes in private sector seed research and development (R&D). We take into account the period after expiration of legal IPP, and require simultaneous equilibrium in markets for R&D, seeds, and final product. Optimal IPP is remarkably insensitive to alternative parameterizations, except for R&D productivity. Results suggest that optimal IPP is greater than IPP in the U.S. seed corn market, but lower than the IPP that could be att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…For instance, the average Canadian now spends less than 10% of his or her income on food (Kirkpatrick and Tarasuk 2003), and this can, arguably, be attributed to the over-production of agricultural commodities, which drives down prices. This was confirmed in a model investigating the impacts of intellectual property protection (IPP) in the seed industry by Lence et al (2005), who found that while farmers might generally lose value because of these protections, the value of the benefits to consumers were always greater than the losses to farmers, and society as a whole received a net benefit with IPP.…”
Section: Societymentioning
confidence: 80%
See 4 more Smart Citations
“…For instance, the average Canadian now spends less than 10% of his or her income on food (Kirkpatrick and Tarasuk 2003), and this can, arguably, be attributed to the over-production of agricultural commodities, which drives down prices. This was confirmed in a model investigating the impacts of intellectual property protection (IPP) in the seed industry by Lence et al (2005), who found that while farmers might generally lose value because of these protections, the value of the benefits to consumers were always greater than the losses to farmers, and society as a whole received a net benefit with IPP.…”
Section: Societymentioning
confidence: 80%
“…This allows for the production of a recombinase which acts to remove the blocking sequence from the terminator gene. opment, genetic diversity enhancement, transgene containment and increased agricultural productivity (Gupta 1998;Lehman 1998;Visser et al 2001;Eaton et al 2002;Goeschl and Swanson 2003;Lence et al 2005). The degree of potential benefits derived from GURTs depends on the social group involved (i.e., private companies, farmers, government or society in general), recognizing of course that these groups are not necessarily mutually exclusive.…”
Section: Potential Benefits Of Gurtsmentioning
confidence: 99%
See 3 more Smart Citations